Impact of maternal diet on the antioxidant status, immune function, and whole-blood selenium levels of lamb offspring - Daniella Hasan; Hunter R. Ford; Massimo Bionaz (Italian Journal of Animal Science)
This study investigated the effects of feeding chicory forage and organic selenium yeast to gestating ewes on their offspring’s antioxidant status, immune functions, and Se status compared to grass forage and inorganic Se injection. Ewes were assigned to one of five treatments (1) grass silage (GCT), (2) grass silage + Se yeast (GSY), (3) chicory silage (CCT), (4) chicory silage + Se yeast (CSY), (5) chicory silage + maternal injection of sodium selenite (GSI). Lambs from GCT and CCT ewes received an injection of sodium selenite three days after birth. An equivalent dose of vitamin E was injected as a control for all ewes and lambs not receiving an injection of sodium selenite. Lambs from chicory-fed dams had increased serum protein, globulin, and ferric reducing antioxidant power (FRAP). The maternal chicory diets also improved lamb serum IgG but not colostrum IgG, indicating improved IgG absorption in lambs whose dams were fed chicory silage. Maternal dietary Se yeast improved lamb Se status and GPx compared to all other treatments. However, a single injection of sodium selenite in the dam or lamb did not improve lamb Se status or GPx activity. These findings suggest that incorporating chicory forage and organic Se sources into maternal diets can optimise antioxidant status, immune function, and Se status in neonatal lambs. The single injection of Se does not seem to be useful, likely because none of our animals were deficient for Se.